2020
DOI: 10.1111/ijcs.12603
|View full text |Cite
|
Sign up to set email alerts
|

Electricity awareness and consumer demand for information

Abstract: With the envisioned growth in the residential electricity demand and increased share of intermittent renewables in the supply mix, consumers will need to be better informed about their electricity consumption and to play an active role in managing their electricity use. However, consumer inattention and lack of information are ubiquitous, especially in household energy‐related settings. Thus, using a novel survey and actual monthly electricity consumption data, this study set out to measure the level of awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 97 publications
1
22
0
Order By: Relevance
“…This could potentially minimize misperceptions about actual financial savings/losses compared to the perceived financial savings/losses and could facilitate optimal (rather than heuristic) decision-making [73]. In addition, by enhancing consumer learning and attention, information provision and awareness about electricity consumption, bills, and tariffs have been shown to increase the price elasticity of demand and to reduce electricity demand [74][75][76][77]. However, a UK study found that [78], even when presented with complete information, many consumers (especially those in the lower socio-economic grades) were affected by bounded 'rationality' and were unable to optimize over their electricity tariff.…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially minimize misperceptions about actual financial savings/losses compared to the perceived financial savings/losses and could facilitate optimal (rather than heuristic) decision-making [73]. In addition, by enhancing consumer learning and attention, information provision and awareness about electricity consumption, bills, and tariffs have been shown to increase the price elasticity of demand and to reduce electricity demand [74][75][76][77]. However, a UK study found that [78], even when presented with complete information, many consumers (especially those in the lower socio-economic grades) were affected by bounded 'rationality' and were unable to optimize over their electricity tariff.…”
Section: Discussionmentioning
confidence: 99%
“…As Sardianou (2007, p. 3784) observed, “energy conscious attitudes do not always lead to conserving behavior”. More recently Trotta (2020) found no relationship between pro‐environmental behavior and energy‐saving behaviors, suggesting that it was financial rather than altruistic motives that influenced household efficiency. Nonetheless, the weight of evidence and intuition suggest that environmentally conscious behaviors will have a relationship with curtailment and investment behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies of household electricity efficiency often try to explain efficiency outcomes, but without considering the effect of interactions between household members (e.g., Dursun et al., 2019; Trotta, 2020). There is, however, growing evidence that interactions within households may influence a range of important environmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The increased wastage of electricity at households arose the importance of electricity consumption behavior, which may significantly impact electricity use and its conservation to overcome its wastage (Trotta, 2021). The mounting research on consumer behavior towards energy conservation gradually improves the understanding to overcome the issue of energy shortage.…”
Section: Introductionmentioning
confidence: 99%
“…However, consumer behavior is complex and challenging to predict accurately (Khan, Ahmed & Najmi, 2019). Scholars have suggested that multiple unknown reasons can instigate electricity conservation, highlighting the need for appropriate theoretical frameworks to uncover these reasons behind such complex consumption behavior (Thøgersen, 2021;Trotta, 2021). The plethora of previous research on the subject notwithstanding, a need is still felt for further exploration into normative and psychological factors related to behavioral intentions.…”
Section: Introductionmentioning
confidence: 99%